Microbial Fuel Cells: Harnessing Bacteria for Sustainable ‎Energy Production - Pradhan , Dr. Sanghamitra; Jayashree , Dr. S.; Sharma , Aakash; Garg , Anvesha; Nagappan, Beemkumar; Kolaventi , Dr. Swarna Swetha; Khurana, Jatin (International Journal of Basic and Applied Sciences, 2025)
Applications of MFCs (Microbial Fuel Cells) are genuinely fascinating! The reducing equivalents produced during the operation of MFCs ‎have a variety of uses, especially in energy generation and waste management. Generally, we can categorize MFC applications into three ‎main areas: power generation, wastewater treatment, and the recovery of valuable byproducts. When substrates are broken down, they ‎release reducing equivalents that interact with an electron acceptor at a specific location in the MFC, called the cathode, which ultimately ‎generates power. Furthermore, while the MFC is operating, certain oxidized metabolites may accept electrons, resulting in the creation of reduced end products with economic value. Beyond these three main applications, there are numerous other fascinating uses for MFCs, depending on their design and operational mode, which can fit into one or more of these categories.
Keywords: MFC; Environments; CO2; Energy; Microbes